Conversion of methane to higher hydrocarbons in pulsed DC barrier discharge at atmospheric pressure - Jeong, HK; Kim, SC; Han, C; Lee, H; Song, HK; Na, BK (KOREAN INST CHEM ENGINEERS, 2001)
Conversion of methane to C-2/C-3 or higher hydrocarbons in a pulsed DC barrier discharge at atmospheric pressure was studied. Non-equilibrium plasma was generated in the barrier discharge reactor. In this plasma, electrons which had sufficient energy collided with the molecules of methane, which were then activated and coupled to C-2/C-3 or higher hydrocarbons. The effect of the change of applied voltage, pulse frequency and methane flow rate on methane conversion, selectivities and yields of products was studied. Methane conversion to higher hydrocarbons was about 25% as the maximum. Ethane, propane and ethylene were produced as primary products, including a small amount of unidentified C-4 hydrocarbons. The selectivity and yield of ethane as a main product cane to about 80% and 17% as the highest, respectively. The selectivities of ethane and ethylene were influenced not by the change of pulse frequency but by the change of applied voltage and methane flow rate. However, in case of propane, the selectivity was independent of those condition changes. The effect of the packing materials such as glass and Al2O3 bead on methane conversion was also considered, showing that Al2O3, played a role in enhancing the selectivity of ethane remarkably as a catalyst.
Keywords: CORONA DISCHARGE; OXIDATIVE DIMERIZATION; NATURAL-GAS; OXIDE; DECOMPOSITION; PLASMA